VAR approach to the determination of interest rates in the Caribbean - Kendall, Patrick ([CCMS] [St. Augustine]TT, 2001)
Seeks to analyse the dynamic interactions among policy action and firm response that yield the interest rate outturns that play such an important role in economic activity.